Screeningempfehlungen für Glaukom, altersabhängige Makuladegeneration und diabetische Augenerkrankungen: Leitthema - Schlößer, Lukas; Ziemssen, Focke; Schuster, Alexander K.; Hasan, Somar; Finger, Robert P. (Die Ophthalmologie, 2025)
Background The main causes of blindness, age-related macular degeneration (AMD), glaucoma and diabetic eye diseases (DED), are becoming increasingly more important in terms of health economics due to the demographic developments. Objective The current screening recommendations for these diseases and the underlying evidence are presented. Material and methods A detailed literature search was conducted and the recommendations of the relevant guidelines of the Association of the Scientific Medical Societies in Germany (AWMF) were summarized. Results There are current screening recommendations for glaucoma and DED but there is still no consensus with respect to AMD. Screening for DED is financed by the statutory health insurance (SHI) and offered as part of routine care. Glaucoma screening is only covered by the SHI if certain risk factors are present and is not yet implemented across the board. Conclusion There are established screening programs for DED that are financed by the SHI; however, there are AWMF recommendations for glaucoma but no SHI-financed screening programs and there are still no AWMF screening recommendations for AMD. Whether and to what extent screening programs are used by the respective target populations should be further investigated in studies.